#TITLE_ALTERNATIVE# - (NIM : 13105090); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, FIRMAN
Piping systems operating at very low temperature requires special consideration since the component will has the propensity of brittle fracture failure. Main characteristic of brittle fracture failure is occurs very quick (usually without warning) and can cause total destructions even the operating load below the design load. To determine whether the component is suitable for further operation or not, it is necessary to conduct some evaluations which called fitness for service. This final project contains study and analysis of fitness for service in piping which has a tendency to brittle fractures failure. FFS analysis performed on propane refrigerant pipes at unit 051, train 1, Tangguh LNG, Papua. To simplify and expedite the analysis, piping calculations program based on level 1 and level 2 assessment criteria has been developed. Based on the assessment level 1, no pipes meet the criteria. Most of pipe with material specifications A671-CC60-22 EFW Impact tested, do not meet level 2 method A - option A (operating pressure/temperature is within a safe envelope - impact test exemption curve) criteria, but it is met the level 2 method A-option B (impact test results) criteria. Most of pipe with material specification A333-6 Seamless ASME PE B36.10M/B36.19M, fulfills the level 2 method A-option A criteria, except pipes with line class 3CA1J, NPS 14-26 and 1CA1J at segment 1051 and 1151. Level 2 method B (hydrotest result) procedure cannot be applied. While, all pipes safe and free from the possibility of brittle fracture, based on Level 2 method C (materials of construction, operating conditions, service environment and past operating experience) analysis.